Directed deadline obligations in agent-based business contracts - Eugénio Oliveira (2010)
There are B2B relationships that presume cooperation in contract enactment. This issue should be taken into account when modeling, for computational handling, contractual commitments through obligations. Deadline obligations have been modeled by considering that reaching the deadline without compliance brings up a violation. When modeling commitments in business contracts, directed obligations have been studied for identifying two agents: the obligation's bearer and the counterparty, who may claim for legal action in case of non-compliance. We argue in favor of a directed deadline obligation approach, taking inspiration on international legislation over trade procedures. Our proposal to model contractual obligations is based on authorizations granted in specific states of an obligation lifecycle model, which we formalize using temporal logic and implement in a rule-based system. The performance of a contractual relationship is supported by a model of flexible deadlines, which allow for further cooperation between autonomous agents. As a result, the decision-making space of agents concerning contractual obligations is enlarged and becomes richer. We discuss the issues that agents should take into account in this extended setting.